TAFSIR AYAT KOMUNIKASI: Dari Komunikasi Qur`ani Menuju Dakwah Humanis - Dawing, Darlis (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2015)
This paper discusses the interpretation clause of Communication in the Qur’an in order to carry the humanist da`wah. Humanist da’wah is determined by effective communication patterns of propagators. On that basis, the study focuses on the effective communication in the Qur’an. The authors trace the interpretation of some verses related to communication with the keywords ’qaul’. In the Qur`an found the word ’qaulan adziman, qaulan balighan, qaulan ma’rufan, qaulan layyinan, qaulan maisuran, qaulan sadidan. With the thematic-combination approach of interpretation, the authors found effective communication possessed distinctiveness of the Qur`an, which is factual, easy to understand, gentle, and full of manners. Communication is the key to success preaching of the apostles.